IMPROVING GAIT REGULARITY AND LOCOMOTOR BALANCE USING FOOTPRINT MARKERS IN STUDENTS WITH PHYSICAL DISABILITIES - Akmal Rizki Hamjah; Hermanto Hermanto; Cepi Safruddin Abdul Jabar; Pujaningsih Pujaningsih; Edi Purwanta (Jurnal Kajian Pendidikan dan Psikologi, 2026)
Locomotor skills are fundamental components of motor development among elementary school students, particularly for students with motor impairments who often experience difficulties in coordination, step regularity, and movement balance. This study aimed to improve step regularity and locomotor movement balance through the implementation of footprint marker media based on the Direct Instruction model among fourth-grade elementary school students with motor impairments. This study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection stages. The research participants were two fourth-grade students with motor impairments at SDN 009 Rantau Pulung. Data were collected through observation, documentation, and field notes, and were analyzed using descriptive quantitative and qualitative approaches. The results showed a gradual improvement in students’ locomotor abilities from the pre-cycle stage to Cycle II. The use of footprint marker media provided visual stimuli that helped students understand stepping patterns and movement directions, while the Direct Instruction model supported learning through demonstration, guided practice, immediate feedback, and gradual reduction of assistance. The findings indicate that the integration of footprint marker media and Direct Instruction effectively improved step regularity, movement balance, and independence among students with motor impairments. This study provides practical implications for the development of adaptive physical education learning that is more concrete, systematic, and inclusive.